2006
DOI: 10.1104/pp.106.077818
|View full text |Cite
|
Sign up to set email alerts
|

RPA, a Class II ARFGAP Protein, Activates ARF1 and U5 and Plays a Role in Root Hair Development in Arabidopsis

Abstract: The polar growth of plant cells depends on the secretion of a large amount of membrane and cell wall materials at the growing tip to sustain rapid growth. Small GTP-binding proteins, such as Rho-related GTPases from plants and ADP-ribosylation factors (ARFs), have been shown to play important roles in polar growth via regulating intracellular membrane trafficking. To investigate the role of membrane trafficking in plant development, a Dissociation insertion line that disrupted a putative ARF GTPase-activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…It was shown recently that AGD10, a class II ARF-GAP, also is important for tip growth in Arabidopsis root hairs. The root hair phenotype of agd10, however, was different from that of agd1 in that agd10 had very short bulbous root hairs and also exhibited defects in pollen germination (Song et al, 2006). This indicates that some of the mechanisms by which AGD10 regulates tip growth in plants might be distinct from those of AGD1.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…It was shown recently that AGD10, a class II ARF-GAP, also is important for tip growth in Arabidopsis root hairs. The root hair phenotype of agd10, however, was different from that of agd1 in that agd10 had very short bulbous root hairs and also exhibited defects in pollen germination (Song et al, 2006). This indicates that some of the mechanisms by which AGD10 regulates tip growth in plants might be distinct from those of AGD1.…”
Section: Discussionmentioning
confidence: 60%
“…AGD10 is more closely related to the mammalian ARF-GAP1, which has a simpler domain organization than the AZAP class of ARF-GAPs to which AGD1 belongs. AGD10 and AGD7, another class II ARF-GAP, only contain a GAP domain and localize to Golgi stacks (Vernoud et al, 2003;Song et al, 2006;Min et al, 2007), in agreement with mammalian ARF-GAP1 localization . AGD1 and AGD3, on the other hand, partially localized to FM4-64-labeled endocytic vesicles and the trans-Golgi network ( Fig.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several reports have shown that small G-proteins and their effectors play important roles in polar growth (e.g., Molendijk et al, 2001;Jones et al, 2002;Preuss et al, 2004;de Graaf et al, 2005;Carol et al, 2005;Gu et al, 2005Gu et al, , 2006Song et al, 2006;Nielsen et al, 2008). Rab11 proteins from mammals are localized in the recycling endosome of polarized epithelial cells.…”
Section: Raba2 Is Important For Genesis and Growth Of The Root Hairmentioning
confidence: 99%